Application of the Quantum Teaching Learning Model to Improve Learning Outcomes of Elementary School Students - Syamsuriyanti Syamsuriyanti; Reski Amalia (Pedagogik Journal of Islamic Elementary School, 2022)
This study aims to improve the learning outcomes of fourth-grade students in social studies subjects in elementary schools. The type of research used was Classroom Action Research (PTK) which involved 39 students and was carried out in two cycles with the stages of implementation, action, observation, and reflection. The results showed that the dingying the Quantum Teaching Learning model could improve social studies learning outcomes, as evidenced by studen,t activity whicentage of 60% in cycle I and increased to 100% in cycle II. In addition, student learning outcomes in cycle I reached a percentage of 51% with an average of 72 and increased to 87% in cycle II with an average of 86. The increase in test results indicated the achievement of indicators of success.